A new genus and species of Katiannidae (Collembola: Symphypleona) from Bolivia - Palacios-Vargas, José G.; Vacaflores-Argandoña, Ma. René (Zootaxa, 2020)
The new genus Borgesminthurinus gen. nov. from Bolivia shares with Sminthurinus the presence of antennal segment IV undivided, antennal segment III with one papilla; sacs of ventral tube smooth; each tenacular rami with 3 teeth and a basal appendix. They also have dens with ventral chaetotaxy reduced and lack mucronal seta; but new genus clearly differs in having thick and barbulate setae on head and body, lacking neosminthuroid setae on abdomen and the presence of seta a0 on Abd. VI acuminate. The new genus differs from Katianna which has divided antennal segment IV, vertex of head with spine-like setae and setae of the body long and smooth.